Analysis of Constitutional Court Decision Number 85/PUU-XIV/2016 Regarding Tender Rigging Practices - Adliakbar, Adliakbar; Ramadhan, Muhammad (LEGAL BRIEF, 2025)
In essence, tender rigging is one form of conspiracy prohibited by Law Number 5/1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition and is also the case most often processed by the KPPU. However, both theoretically and practically, it raises problems, namely because of the biased interpretation of the phrase "other party" in Article 22 of Law Number 5/1999. This is the background to the judicial review of Article 22 to the Constitutional Court. In this paper, what is discussed is how tender rigging is regulated according to laws and regulations, what are the legal implications of the Constitutional Court Decision Number 85/PUU-XIV/2016 concerning the judicial review of Article 22 of Law Number 5/1999 and how the legal analysis of the legal considerations of the Constitutional Court Decision. This study uses normative legal research where the object of this research is laws and regulations and the Constitutional Court Decision. In this case, the Author concludes, namely, First, tender collusion which is a form of cooperation between two or more parties to control the relevant market and/or win tender participants resulting in unfair business competition is explicitly regulated in Article 1 number 8 and Article 22 of Law Number 5/1999 and KPPU Regulation Number 2/2010, Second, the legal implications of the Constitutional Court Decision Number 85/PUU-XIV/2016 are useful for ensuring legal certainty and justice for parties such as entrepreneurs, especially the community. For this reason, there needs to be harmonization between one regulation and another, testing of the Law against the Constitution related to the regulation of tender collusion in unfair business competition or revision of Law Number 5/1999.